Prolyl hydroxylation in elastin is not random - Schmelzer, Christian E.H.; Nagel, Marcus B.M.; Dziomba, Szymon; Merkher, Yulia; Sivan, Sarit S.; Heinz, Andrea (Biochimica et biophysica acta, 2016)
This study aimed to investigate the prolyl and lysine hydroxylation in elastin from different species and tissues. Enzymatic digests of elastin samples from human, cattle, pig and chicken were analyzed using mass spectrometry and bioinformatics tools. It was confirmed at the protein level that elastin does not contain hydroxylated lysine residues regardless of the species. In contrast, prolyl hydroxylation sites were identified in all elastin samples. Moreover, the analysis of the residues adjacent to prolines allowed the determination of the substrate site preferences of prolyl 4-hydroxylase. It was found that elastins from all analyzed species contain hydroxyproline and that at least 20%–24% of all proline residues were partially hydroxylated. Determination of the hydroxylation degrees of specific proline residues revealed that prolyl hydroxylation depends on both the species and the tissue, however, is independent of age. The fact that the highest hydroxylation degrees of proline residues were found for elastin from the intervertebral disc and knowledge of elastin arrangement in this tissue suggest that hydroxylation plays a biomechanical role. Interestingly, a proline-rich domain of tropoelastin (domain 24), which contains several repeats of bioactive motifs, does not show any hydroxyproline residues in the mammals studied. The results show that prolyl hydroxylation is not a coincidental feature and may contribute to the adaptation of the properties of elastin to meet the functional requirements of different tissues. The study for the first time shows that prolyl hydroxylation is highly regulated in elastin. [Display omitted] •Elastins from human, cow, pig and chicken show prolyl but no lysyl hydroxylation.•Prolyl hydroxylation is dependent on tissue and species, but independent of age.•Exact hydroxylation sites in elastin and preferences of P4H were determined.•Highest hydroxylation degrees were found for elastin from the intervertebral disc.